STRATEGI E-BISNIS DALAM MENINGKATKAN EFISIENSI PRODUKSI DAN PEMASARAN BOTOL PLASTIK: STUDI KASUS PT ASIA PRAMULIA SURABAYA - Laili Alnur Rofa; Sri Lestari (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2024)
The research aims to analyze the e-business strategies implemented by PT Asia Pramulia Surabaya in enhancing the efficiency of production and marketing of plastic bottles. With a focus on PT Asia Pramulia Surabaya, the study seeks to identify how e-business strategies have impacted the company's production efficiency, including increased productivity, cost reduction, and manufacturing process optimization, to understand the effects of e-business strategies on the marketing of plastic bottle products. The research employs a qualitative research method with a case study approach. The findings of this research are presented in three main sub-sections: analysis of e-business strategies at PT Asia Pramulia Surabaya, the influence of e-business strategies on operational efficiency, and an evaluation of digital marketing strategies at PT Asia Pramulia Surabaya.